Risiko Kredit, Risiko Pasar, Dan Kinerja Keuangan Perbankan Pada Masa Pandemi Covid-19 - Astuti, Rini Dwi; Mahardika, Dewa Putra Krishna (JURNAL MUTIARA AKUNTANSI, 2021)
The Covid-19 pandemic began to spread in Indonesia in March 2020. This caused a number of industrial sectors in Indonesia to experience a decrease in financial performance. One of the sectors that experienced a decline in financial performance was the banking sector. This study has purpose to determine the effect of credit risk and market risk on financial performance in commercial banks registered on the Indonesia Stock Exchange in the first until fourth quarters of 2020. The samples in this study is 35 banks. The sample is obtained by purposive sampling method. The method of analysis in this study is multiple linear regression analysis. From the results of the study, simultaneously credit risk and market risk affect financial performance. credit risk negatively affects financial performance. while market risk has a positive effect on financial performance